Philippine history - Francisco, Paul Micah S.; Francisco, Virlyn Jaime (Mindshapers Co., Inc., 2015)
"The book is basically divided into different eras of the Philippine History. The Pre Colonial Era where the authors used primary sources to discuss the different areas of the Philippine society because this could be the source of self pride among Filipinos. The second part is the Colonial where the authors narrated the events during the Spanish, American and Japanese era using the Filipino perspective and they used scholarly works of the authors, and the Contemporary Era where the authors related the past to the present"--Preface